The electricity before Faraday - Gabriel Poveda-Ramos (Revista Facultad de Ingeniería Universidad de Antioquia, 2003)
This document is a paper describing the appearance and development of the electrical science since the early human history until the times of Michael Faraday at the beginning of nineteenth century. It is writen with the pourpose of adding it to another paper already writen by the author on the history of magnetism in the same period.